The Integration Patterns in East Asia: A Test by the European Union Experience - Andrey Anatolyevich Baykov (Сравнительная политика, 2015)
The article focuses on a comparative analysis of the two modern centers of integration, Europe and East Asia. The author criticizes the Eurocentric theories of integration, analyzes the stages and features of integration projects in the European Union and the Association of Southeast Asian Nations, identifying similarities and differences of the integration in the both international regions.